Aplikasi Pendekatan Kritis-Historis (Geschichte Des Qorans) Theodor Noldeke (1837-1930) Dalam Studi Al-Qur’an - Hilmy Pratomo (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2018)
Al-Qur`an is a holy book that is tanawwu' al-wujûh (can be studied from varioussides). From here the Qur`an is opened to study with a variety approaches byinsider and outsider (orientalis). There are at least three tendencies of Orientaliststudies of the Qur`an, firstly, they want to show the influence of the Jewish andChristian traditions in the Qur`an, secondly, focusing on discussing the history andchronology of the Qur`an, thirdly, Orientalist studies that discuss certain themes inthe Qur`an. Based on the mapping results above, Theodor Noldeke entered the firstgroup. Noldeke examined the influence of Jewish and Christian traditions in theQur`an earlier considering that the Qur`an was coming down more recently. Inconducting his study Noldeke used a historical critical approach (historicalcriticism). The result was that Noldeke saw the Qur`anic influence from Jewish andChristian traditions. This can be seen from the stories in the Qur`an that resemblethe stories in the old testament, only the version of the Qur`an has been added fromthe original form. The stories taken from the new covenant are legend stories(usṭûriyah), such as the story of Mary and the birth of Jesus. According to Noldeke,other evidence of influence is also found in Basmalah utterances.